Study of Electronegativity and Inductive Effect in Polar-Non Polar Liquid Mixtures - VIJAYALAKSHMI, K.; LALITHA, V. (Asian Journal of Chemistry, 2010)
Infrared spectra of several hydrogen bonded liquids in the pure state and their mixtures are recorded using Perkin Elmer 577 IR spectrophotometer. The alcohols from methanol upto hexanol and dioxane are taken for study. The neat spectra of the mixtures of various proportions are recorded at 25 ºC. Variation of absorbance A of various modes of vibrations of the mixtures with respect to concentration and wave number are used for the study of interaction between the pure liquids.